Marrying mussel inspired chemistry with SET‐LRP: A novel strategy for surface functionalization of carbon nanotubes. Issue 16 (8th April 2015) - Tian, Jianwen; Xu, Dazhuang; Liu, Meiying; Deng, Fengjie; Wan, Qing; Li, Zhen; Wang, Ke; He, Xiaohui; Zhang, Xiaoyong; Wei, Yen
ABSTRACT Surface functionalization of carbon nanotubes (CNTs) with a thermo responsive polymer was achieved via combination of mussel inspired chemistry and surface initiated single electron transfer living radical polymerization (SET‐LRP). In this procedure, CNTs were first coated with polydopamine (PDA) through self polymerization under a rather mild condition. And then PDA functionalized CNTs bearing with amino and hydroxyl groups were further reacted with bromo isobutyryl bromide. Finally, a thermo responsive polymer poly(N‐isopropylacrylamide) (PNIPAM) was introduced on the CNTs via SET‐LRP. The successful surface modification of CNT‐PDA‐PNIPAM was evidenced by a series of characterization techniques. The resulting CNT‐PDA‐PNIPAM showed significant enhancement of dispersibility in both aqueous and organic solvents. More importantly, these CNT‐polymer nanocomposites showed obvious thermo responsive behavior due to the surface coating CNTs with PNIPAM. As compared with previous methods, this method is not required oxidation of CNTs to introduce funcitonal groups for immobilization of the polymerization initiators. More importantly, this method could also be utilized for fabricating many other polymer nanocomposites because of the strong and universal adhesive of PDA to various materials. It is therefore, the novel strategy via marrying mussel inspired chemistry with SET‐LRP should be a simple, general and effective method for surface functionalization. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 1872–1879